General mutation databases: analysis and review. Issue 2 (24th September 2007) - George, R A; Smith, T D; Callaghan, S; Hardman, L; Pierides, C; Horaitis, O; Wouters, M A; Cotton, R G H
Abstract : Databases of mutations causing Mendelian disease play a crucial role in research, diagnostic and genetic health care and can play a role in life and death decisions. These databases are thus heavily used, but only gene or locus specific databases have been previously reviewed for completeness, accuracy, currency and utility. We have performed a review of the various general mutation databases that derive their data from the published literature and locus specific databases. Only two—the Human Gene Mutation Database (HGMD) and Online Mendelian Inheritance in Man (OMIM)—had useful numbers of mutations. Comparison of a number of characteristics of these databases indicated substantial inconsistencies between the two databases that included absent genes and missing mutations. This situation strengthens the case for gene specific curation of mutations and the need for an overall plan for collection, curation, storage and release of mutation data.